PERSEPSI PELANGGAN TERHADAP PELAYANAN PUBLIK DI KANTOR PERTANAHAN KABUPATEN MAGELANG - , ADI CAHYANTO, S.Si.T ([Yogyakarta] : Universitas Gadjah Mada, 2011)
ReformsÂ  undertakenÂ  byÂ  manyÂ  publicÂ  serviceÂ  agenciesÂ  becauseÂ  ofÂ  theÂ influenceÂ ofÂ regionalÂ autonomyÂ andÂ decentralizationÂ littleÂ influenceÂ onÂ whetherÂ orÂ  notÂ  alsoÂ  provideÂ  servicesÂ  ofÂ  theÂ  LandÂ  OfficeÂ  asÂ  verticalÂ  institutionÂ  NationalÂ LandÂ AgencyÂ ofÂ RepublicÂ ofÂ IndonesiaÂ inÂ eachÂ districtÂ /Â city.Â AlthoughÂ itÂ isÂ stillÂ aÂ centralizedÂ hierarchy,Â butÂ becauseÂ theÂ regionÂ isÂ inÂ anÂ environmentÂ  ofÂ  localÂ governmentÂ district,Â theseÂ agenciesÂ willÂ alsoÂ inevitablyÂ influencedÂ  byÂ  bothÂ positiveÂ andÂ negativeÂ inÂ termsÂ ofÂ provisionÂ andÂ managementÂ ofÂ landÂ services.Â PublicÂ opinionÂ inÂ  MagelangÂ regency,Â thatÂ  theÂ publicÂ  serviceÂ inÂ  MagelangÂ DistrictÂ LandÂ OfficeÂ thereÂ areÂ stillÂ gapsÂ betweenÂ theÂ expectationsÂ ofÂ Â theÂ Â desiredÂ Â applicantÂ (customer)Â withÂ theÂ  factÂ theÂ  qualityÂ  ofÂ servicesÂ providedÂ  byÂ theÂ  LandÂ Office.Â Â  IfÂ theÂ  serviceÂ  providedÂ  isÂ notÂ qualifiedÂ thenÂ  theÂ customersÂ areÂ  reluctantÂ Â toÂ comeÂ toÂ  theÂ  LandÂ  OfficeÂ andÂ isÂ  fearedÂ trustÂ buildingÂ willÂ decline,Â  especiallyÂ inÂ communitiesÂ whichÂ inÂ turnÂ willÂ affectÂ theÂ investmentÂ inÂ theÂ region.Â Â UsingÂ surveyÂ researchÂ withÂ aÂ qualitativeÂ approachÂ andÂ thenÂ attemptÂ  toÂ explainÂ howÂ customerÂ perceptionsÂ ofÂ theÂ qualityÂ ofÂ publicÂ servicesÂ inÂ MagelangÂ DistrictÂ  LandÂ  OfficeÂ  inÂ  accordanceÂ  withÂ  theÂ  dimensionsÂ  ofÂ  trust.Â AndÂ  provideÂ focusÂ  itsÂ  attentionÂ  onÂ  threeÂ  indicatorsÂ  ofÂ  trust,Â  namely:Â  ability,Â  benevolence,Â integrity.Â FromÂ theÂ resultsÂ ofÂ researchÂ withÂ 52Â respondentsÂ fromÂ theÂ public,Â  theÂ authorÂ  illustratesÂ  thatÂ  theÂ  MagelangÂ  DistrictÂ  LandÂ  OfficeÂ  inÂ  providingÂ  publicÂ servicesÂ toÂ customersÂ inÂ wellÂ categorized.Â TheÂ averageÂ valueÂ ofÂ answersÂ toÂ questionsÂ  answeredÂ  questionnairesÂ  stronglyÂ  agreeÂ  (SS)Â  numberÂ  ofÂ  26Â respondentsÂ  (50.0%)Â  whileÂ  theÂ  answerÂ  doesÂ  notÂ  agreeÂ  (TS)Â  byÂ  8Â  respondentsÂ (15.4%),Â  theÂ  remainingÂ  numberÂ  ofÂ  18Â  (34.6%)Â respondentsÂ  answeredÂ  agreeÂ (S).Qualitatively,Â  respondentsÂ  showÂ  satisfactionÂ  relatedÂ toÂ  ability,Â  benevolence,Â andÂ integrityÂ ofÂ publicÂ servicesÂ inÂ MagelangÂ DistrictÂ LandÂ Office.Â AbilityÂ (ability)Â BPNÂ  officersÂ  MagelangÂ  regency,Â  inÂ  theÂ  formÂ  ofÂ  administrativeÂ  servicesÂ  thatÂ facilitateÂ andÂ prioritizeÂ customer.Â RespondentsÂ  alsoÂ  identifiedÂ aÂ simpleÂ interactionÂ  isÂ  established,Â  skilledÂ  employeesÂ  whoÂ  workÂ  fast,Â  andÂ  thorough.Â BenevolenceÂ appearÂ atÂ theÂ therapeuticÂ patternsÂ ofÂ communication,Â servicesÂ thatÂ provideÂ  convenience,Â  andÂ  theÂ  attitudeÂ  ofÂ  serviceÂ  thatÂ  respondsÂ  toÂ  customerÂ needs.Â TherapeuticÂ  CommunicationÂ  ServiceÂ  employeesÂ  effectiveÂ  BPNÂ  MagelangÂ respondents.RespondentsÂ  alsoÂ  identifiedÂ  integrityÂ  BPNÂ  officersÂ  MagelangÂ DistrictÂ  inÂ  accessingÂ  landÂ  information,Â  candorÂ  andÂ  fulfillmentÂ  ofÂ  customerÂ complaints.Â ThereÂ isÂ littleÂ difficultyÂ aboutÂ theÂ candorÂ ofÂ BPNÂ staffÂ inÂ providingÂ publicÂ servicesÂ andÂ fulfillmentÂ ofÂ customerÂ complaints.Â TheseÂ obstaclesÂ canÂ beÂ resolvedÂ withÂ openÂ dialogueÂ opportunitiesÂ betweenÂ providerÂ withÂ customersÂ inÂ anÂ effortÂ toÂ  seekÂ  agreementÂ  toÂ  settleÂ  theÂ  problemÂ  inÂ  publicÂ  serviceÂ  inÂ  MagelangÂ  DistricÂ LandÂ Office.Â